PENGARUH LIKUIDITAS, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN MAKANAN DAN MINUMAN TAHUN 2019-2021 - Rani Rahmawati; Endang Marsitoh; Purnama Siddi (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
The purpose of this study is to test and analyze whether liquidity, firm size, and leverage have an effect on firm value. The secondary data are obtained from the financial statements of food and beverage business entities listed on the Indonesia Stock Exchange (IDX) for the period 2019-2021.The population uses the food and beverage business sector listed on the Indonesia Stock Exchange (IDX) for the period 2019-2021. The population is the food and beverage business entities listed on the Indonesia Stock Exchange (IDX) for the period 2019-2021. The sample was taken using purposive sampling technique, and obtained a sample that met the criteria of 18 business entities. Data analysis was done using multiple linear regression analysis technique, which was processed using SPSS version 21. The results indicated that there was an effect of liquidity and firm size on the value of the firm, while leverage had no effect on the value of the firm.